Occupational Exposure to Blood and Body Fluids in a Department of Oral Sciences: Results of a Thirteen-Year Surveillance Study. (14th February 2013) - Gatto, M. R. A.; Bandini, L.; Montevecchi, M.; Checchi, L.
Abstract : Objectives. Aim of this analysis was to identify trends that will aid in the prevention of injury. Methods. Our data were collected from 1999 to 2011 during a surveillance program of occupational exposures to blood or other potentially infectious materials in a Dental School by using a standard coded protocol. Results. 63 exposures were reported. 56/63 (89%) percutaneous and 7/63 (11%) mucosal, involving a splash to the eye of the dental care workers (DCW). 25/63 (40%) involved students, 23/63 (36%) DCW attending masters and doctorate, 13/63 (21%) DCW attending as tutors and 2/63 (3%) staff. 45/63 (71%) and 18/63 (29%) occurred respectively during and after the use of the device; of last ones, 1/18 (0.05%) were related to instrument clean-up and 1/18 (0.05%) to laboratory activity, 12/18 (67%) occurred when a DCW collided with a sharp object during the setting, and 4/18 (22%) during other activities. The instrument and the body part most likely involved were needle and finger respectively. The overall exposure rate was 4.78 per 10, 000 patient visits. Conclusions Our results may serve as benchmark that Dental Schools can employ to assess their frequency of injury.